Association between gastrointestinal complaints and psychopathology in patients with anorexia nervosa. Issue 5 (10th February 2020) - Kessler, Ute; Rekkedal, Guro Å.; Rø, Øyvind; Berentsen, Birgitte; Steinsvik, Elisabeth K.; Lied, Gülen A.; Danielsen, Yngvild
Abstract: Objective: Gastrointestinal (GI) symptoms appear frequently in patients with anorexia nervosa (AN), but the associations between psychopathological, GI, and eating disorder (ED) symptoms remain unclear. This study aimed to determine the relationships of GI complaints with psychopathological measures, ED symptoms, and body mass index (BMI) in patients with AN. Method: Thirty outpatients with AN aged >16 years were included. Psychopathological measures (Symptom Checklist‐90‐Revised, Beck Depression Inventory‐II, and Beck Anxiety Inventory), ED symptoms (Eating Disorder Examination Questionnaire), ED‐associated impairment (Clinical Impairment Assessment Questionnaire), GI complaints (Irritable Bowel Syndrome Severity Scoring System [IBS‐SSS]), and BMI were assessed prior to starting treatment, and correlation and multiple regression analyses were applied to data from 19 patients. Results: IBS‐symptoms were significantly correlated only with ED symptoms ( r = 0.583, p = .009) and somatization ( r = 0.666, p = .002). Multiple regression analysis revealed that somatization significantly predicted worse IBS symptoms (beta = 0.5, p = .04), while ED symptoms did not. Discussion: Higher IBS‐SSS scores were associated with higher severities of other somatic complaints. GI complaints and somatization should be addressed in treatments for AN in order to prevent these factors impeding the establishment of healthy eating patterns. Clinical trial registration: ClinicalTrials.gov Identifier: NCT02745067.